West meets East building theoretical bridges - Wang, Catherine L.; Ketchen, David J.; Bergh, Donald D. (Emerald, 2012)
This book series' mission is to provide a forum for critique, commentary and discussion about key methodology issues in the strategic management field. Strategic management relies on an array of complex methods drawn from various allied disciplines to examine how managers attempt to lead their firms toward success. The eighth volume of the series is built around the theme of "West Meets East: Building Theoretical Bridges". Within this overarching theme, this volume consists of two parts. The first is "Methods for Discovery and Theory Building" and the second is "Western Theories and Concepts in the Eastern Context". While the contributors of this volume are from an array of country backgrounds including Australia, China, Denmark, Germany, Korea, New Zealand, Singapore, Spain, Taiwan, the UK and the USA, the majority of the chapters refer to Asia, especially China, as the powerhouse of the global economic growth. We hope that the methodological insights offered in this volume will help build the theoretical bridges between the West and the East.
Keywords: Strategic planning -- Asia.; elektronické knihy; electronic books